PCB2 improves porcine oocyte maturation by enhancing TZP-mediated cumulus-oocyte communication - Yuwen Luo; Qingrui Zhuan; Dan Zhou; Hongyu Liu; Jun Li; Xiangwei Fu (Theriogenology, 2026)

Effects of topographic factors on soil bioavailable cadmium and arsenic in typical microtopographic rice-growing areas of hilly southern China - Tao Xue; Faxiang Tian; Haoyu Chen; Zhaobing Liu; Xionghui Ji; Hongyu Fu; Yunhe Xie (Journal of Hazardous Materials, 2026)

Simultaneous adsorption of polystyrene nanoplastics and phosphorus by a magnetic calcium-modified biochar from aqueous solutions: Mechanism and applications - Jingran Fu; Zelong Wang; Sishi Liu; Maoyu Jiao; Shefeng Li; Siyu Ding; Yong Zhang; Xuli Li; Haijun Lu; Jing Zhang; Hongyu Wang (Journal of Environmental Chemical Engineering, 2026)

The boosted light utilization and spatial charge separation efficiency of ZnIn2S4 photoanode for photoelectrochemical hydrogen evolution by synergistical action of non-metal plasmonic effect and charge transport channel - Kangwei Zhang; Guozhong Wei; Bufan Liu; Hongyu Wang; Ruoyi Jin; Lang Cheng; Ziyi Wang; Zhen Qu; Junli Fu; Guling Zhang; Wenzhong Wang (Journal of Environmental Chemical Engineering, 2026)

Window-specific effects of ultraviolet radiation and air pollution on ovarian reserve in infertile women: A retrospective cohort study - Qi Tang; Cong Fu; Hongyu Du; Qing Liu; Kui Yang; Zhuoni Xiao; Yanqing Xu (Environmental Pollution, 2026)

Promoting mechanism of weathered coal on methane production from anaerobic digestion of pig manure - Hongyu Guo; Yuanbo Dou; Xiao Zhou; Wen Fu; Hengxing Ren; Changjiang Ji; Lijiao Yue; Shufeng Zhao; Shuaishuai Xu (Biomass and Bioenergy, 2026)

Comprehensive assessment of soil health in typical pear orchards in Northwest China - Hongyu Yu; Zhibing Zheng; Bingyue Yu; Xin Wang; Ze Yuan; Kuan Xu; Chen Fu; Tianchi Jiang; Jiapan Lian; Pengfei Liu; Binggan Lou; Wolde tefera; et al. (Soil and Tillage Research, 2026)

Protector or provocateur? Analysis of U.S. overseas military bases and terrorism - Ming Yan; Cong Fu; Hongyu Du; Deirdre Conlon; Shuang Zhao; Ruidun Chen; Silas Nogueira de Melo; Yuchen Li; Yanqing Xu (Applied Geography, 2026)

Unraveling water sources and groundwater discharge in Mu Us Desert lakes using coupled 222Rn-2H-18O and hydrochemical tracers - Fengxia Liu; Guangcai Wang; Fu Liao; Hanxiao Wang; Xinming Song; Zheming Shi; Hongyu Zhang (Journal of Hydrology, 2026)

Crab tracking and activity estimation method based on YOLOv11-BoT-SORT - Fu Jiayi; Kong Mingrui; Pan Hongyu; Li Chenlong; Duan Qingling (Aquaculture International, 2026)

New healthcare management framework informed by peri-body perception space: a perspective - Chaoqun Dong; Yan Ji; Ruzhen Luo; Xuemei Fu; Zhongmin Fu; Yingying Huang; Ting Yi; Zhifei Chen; Yiwen Hu; Ziqi Chen; Shimeng Dai; Guangming Tao; et al. (EPMA Journal, 2026)

Ferroptosis mediated by aggregation of Triosephosphate isomerase 1 links cadmium exposure to pulmonary fibrosis - Yishan Yin; Xuehan Jiang; Jiayi Li; Hongxue Yang; Yi Fang; Bo Li; Hongyu Fu; Jingzeng Cai; Ziwei Zhang (Chemico-Biological Interactions, 2026)

Effects of microplastics on carbon and nitrogen cycling in coastal wetlands: A critical meta-analysis - Feng Yuan; Hongyu Chen; Yue Xue; Yongcheng Ding; Qiujun An; Zhian Hu; Yifei Qiu; Jianguo Tao; Jin Luo; Guanghe Fu; Teng Wang; Xinqing Zou (Water Research, 2026)

Local mitigation, regional leakage? Climate effects of sustainable development policy in China’s resource-based cities - Liyun Wang; Hongyu Cai; Xu Fu; Guoying Deng (Urban Climate, 2026)

Iron plaque crystallinity driven by phosphorus gradients directs Cd/As partitioning in rice - Jibo Long; Qian Zhu; Hongyu Fu; Bingyu Li; Yimin Zhou; Zhuoqing Li; Jiaxiang Wang; Cheng Qiu; Qinghai Liu; Ming Lei (Cereal Research Communications, 2026)

Synergistic organic amendments show broad potential for context-specific regulation of soil available iron in croplands - Hongyu Yu; Bingyue Yu; Erxu Xue; Chen Fu; Jing Chen; Ruiqi Yao; Pengfei Liu; Binggan Lou; Qingxu Ma; Li Chen; Kuan Xu; Jiuzhou Chen; et al. (Applied Soil Ecology, 2026)

Natural and anthropogenic controls on rare earth elements in groundwater: Indicative significance for distinguishing agricultural and urban-industrial impacts - Hang Meng; Guangcai Wang; Fu Liao; Hairu Mao; Bo Li; Fengxia Liu; Xianglong Chen; Hongyu Zhang; Zhiyuan Qiao (Journal of Hazardous Materials, 2026)

The Protective Role of Selenium Against Thyroid Injury in Pigs: Involvement of PINK1/Parkin-Mediated Mitophagy and Apoptosis Regulation - Xuehan Jiang; Yishan Yin; Yi Fang; Hongxue Yang; Hongyu Fu; Bo Li; Xiaoxiao Chen; Bendong Shi; Jingzeng Cai; Ziwei Zhang (Biological Trace Element Research, 2026)

The plant ontology of cell types - Hongyu Chen; Pu Liang; Xiaolin Lu; Shuai Jiang; Jingjing Jin; Jiaqi Cai; Yaqian Lu; Dihuai Zheng; Jie Yao; Qinjie Chu; Huixia Shou; Chengxin Fu; et al. (Molecular Plant, 2026)

Retrogressive thaw slump expansion and vegetation phenological response in the Qilian Mountains, northeastern Tibetan Plateau - Xiaoying Yang; Tanguang Gao; Ningjing Tan; Yujiao Zhao; Jiaxing Fu; Hongyu Zhang; Xuexue Shang (Journal of Mountain Science, 2026)

Pollutant emission reductions contributed to reducing nitrate level in regional-scale groundwater - Hairu Mao; Guangcai Wang; Fu Liao; Fei Liu; Zheming Shi; Pengpeng Zhou; Chenyu Wang; Hongyu Zhang; Yuqin Wang; Yunfei Bai; Xianglong Chen (Journal of Hydrology, 2026)

Organic molecule functionalization of Cu single-atom catalysts for enhanced electrocatalytic CO2 reduction to methane - Yihai Wu; Zhenchao Xu; Jianglan Chen; Hongyu Li; Yu Fu; Yuhan Sun; Jun Zhang (Journal of Environmental Chemical Engineering, 2026)

Pectic polysaccharides from Mongolian medicinal Hypecoum leptocarpum: Structure and ulcerative colitis amelioration via gut microbiota and intestinal inflammation regulation - Cunwuliji Na; Xiang Shi; Jicheng Fu; Jiahao Li; Hongyu Jiang; Zhiwei Guo; Hongyan Lai; Zhipeng Zhang; Longyan Zhao; Qingxia Yuan; Baoshun Zhang (Carbohydrate Polymers, 2026)

Do biodegradable plastic residues pose lower ecological risks to crops than conventional plastic residues? A meta-analytic comparison - Feng Yuan; Teng Wang; Hongyu Chen; Yongcheng Ding; Jianguo Tao; Yue Xue; Linjie Zhang; Haiyan Lin; Baojie Li; Yifei Qiu; Guanghe Fu; Xinqing Zou (Journal of Hazardous Materials, 2026)

The comprehensive fingerprints of VOCs from complex coking emissions and their temporal evolution in the atmosphere based on backward inference method - Hongyan Li; Shidan Huang; Yuanchun Ren; Yanru Zhang; Jing'’ai Bai; Hongyu Li; Guozhong Zhang; Xueying Gao; Yang Cui; Lili Guo; Jie Fan; Yongchun Liu; et al. (Atmospheric Research, 2026)

Differences in Neurofilament Light Chain, Glial Fibrillary Acidic Protein, and Tau Protein Levels in Patients with Temporal Lobe Epilepsy and Comorbid Depression - Ziting Kong; Junling Fu; Huazheng Luo; Canmei Su; Limei Diao; Qianchao He; Hongyu Xu; Xinmei Zhou; Yiliu Xiao; Cui Qin; Lun Cai (Molecular Neurobiology, 2026)

Metagenomic insight into the ecological effects of the plastisphere in coastal salt marshes - Feng Yuan; Junjie Wang; Ming Lu; Qihang Liao; Teng Wang; Yue Xue; Hongyu Chen; Yongcheng Ding; Guanghe Fu; Penghua Qiu; Xinqing Zou (Marine Pollution Bulletin, 2025)

Preparation of Prussian blue analogues and investigation of their micro-ammonia adsorption properties - Guancheng Wang; Abdulla Eziz; Abulikemu Abulizi; Hongyu Fu; Kenji Okitsu; Tiezhen Ren; Aisha Nulahong (Journal of Environmental Chemical Engineering, 2025)

The SDGSAT-1 mission and its role in monitoring SDG indicators - Huadong Guo; Changyong Dou; Dong Liang; Bihong Fu; Hongyu Chen; Ziming Zou; Peng Huang; Xiaoming Li; Fansheng Chen; Chengshan Han; Juanjuan Jing; Tai Hu; et al. (Remote Sensing of Environment, 2025)

The impacts of polypropylene microplastics on carbon and nitrogen cycling in coastal wetlands: Field evidence - Feng Yuan; Yue Xue; Zhuoyue Zhang; Jianguo Tao; Yuyang Song; Hongyu Chen; Qihang Liao; Haiyan Lin; Ming Lu; Yongcheng Ding; Teng Wang; Ruize Yang; et al. (Journal of Hazardous Materials, 2025)

ZnO/LIG nanocomposites to detect acetone gas at room temperature with high sensitivity and low detection limit - Li Yang; Wenyuan Fu; Ya Wang; Zhida Wang; Longbiao Mao; Luxiang Xu; Chengpeng Yao; Hongyu Zhang; Sisi Chen; Hui Zhang; Huanyu Cheng (Chemical Engineering Journal, 2025)

Modulation of strategic status signaling: oxytocin changes men’s fluctuations of status products preferences in their female partners’ menstrual cycle - Honghong Tang; Hongyu Fu; Song Su; Luqiong Tong; Yina Ma; Chao Liu (Psychopharmacology, 2025)

Delta-scale mapping of coastal erosion vulnerability at the modern Yellow River Delta and implications for geomorphic sustainability - Hongyu Ji; Xuelei Gong; Yaoshen Fan; Yuanbin Fu; Hanghang Lyu; Peng Li; Yin Cao; Shenliang Chen; Shentang Dou (Ocean & Coastal Management, 2025)

Experimental research and application of a new no-pillar green coal mining method - Qiang Fu; Jun Yang; Yubing Gao; Hongxu Song; Yuxuan Liu; Hongyu Jin; Jiarui Tang; Junpeng Zhao; Jianbo Cui (Bulletin of Engineering Geology and the Environment, 2025)

Effect of hazelnut protein oxidation on O/W emulsion stability, interfacial properties and lipid oxidation based on hazelnut protein oxidation - Ziyi Huang; Yanyan Wu; Le Chen; Hongyu Jiang; Chuan Tian; Miao Fu; Chunmao Lyu (Journal of Stored Products Research, 2025)

Evaluation of quality characteristics of hazelnut using infrared assisted enzymatic peeling technology - Le Chen; Ziyi Huang; Yanyan Wu; Hongyu Jiang; Chuan Tian; Miao Fu; Chunmao Lyu (Food Control, 2025)

Research on the short-process of leaching and semi-extraction method of nickel‑cobalt from mixed hydroxide precipitate (MHP) to prepare battery grade products - Yukun Shen; Hongyu Wang; Liang Zhang; Liyong Zhou; Chunping Fu; Kweon Ho Jin; Mingkang Fang; Jiade Wang (Hydrometallurgy, 2025)

Activation of persulfates on carbon nanotubes for water decontamination: Is the non-radical process consistently considered across different pH levels? - Jiali Peng; Lun Li; Shihuai Deng; Hongyu Zhou; Yanjun Li; Chenye Fu; Long Lin; Yue Yuan; Wei Wei; Guochun Lv; Gang Yang; Xiaohui Lu; et al. (Journal of Hazardous Materials, 2025)

Ground response during of EPB shield shutdown in gravel ground based on coupled CEL-FEM analysis - Jinyang Fu; Jichen Xie; Hongyu Zhang; Haoyu Wang; Shuying Wang; Junsheng Yang (Computers and Geotechnics, 2025)

Effect of chlorine dioxide (ClO2) combined with different oxygen permeability package treatments on postharvest antioxidant activity and storage life of ‘Liaofeng’ grapes - Yanyan Wu; Le Chen; Ziyi Huang; Chuan Tian; Hongyu Jiang; Miao Fu; Chunmao Lyu (Food Control, 2025)

Impact of land covers on pesticide contamination and the associated ecological risk in a major tributary of the Pearl River, South China - Kaiyi Wu; Qilong Liao; Chengzhong Fu; Weikeng Luo; Qiyuan Lu; Bowen Li; Hongyu Fu; Zhongwen Li; Guangyu Liao; Bin Tang; Jing Zheng (Science of The Total Environment, 2025)

Regularization by double complementary priors for full waveform inversion - Hongyu Qi; Zhenwu Fu; Yang Li; Bo Han; Longsuo Li (Computers & Geosciences, 2025)

Effect of simultaneously addition of Fe3+ and reed straw biochar on nitrogen removal efficiency and GWP for Anammox - Jingran Fu; Huan Liao; Zelong Wang; Yaxuan Xiao; Yi Zhang; Guoliang Bai; Jing Zhang; Hongyu Wang; Haijun Lu; Yiqie Dong; Xinghua He (Chemical Engineering Journal, 2025)

Surfactant-modified ZnFe2O4/CaOPS porous acid-base bifunctional catalysts for biodiesel production from waste cooking oil and process optimization - Hongyu Fu; Yunxue Xiao; Abulikemu Abulizi; Kenji Okitsu; Yasuaki Maeda; Tiezhen Ren (Journal of Environmental Chemical Engineering, 2024)

Stress Field Comparison in Deep Coal Mines: Roof Cutting Versus Traditional Methods - Jun Yang; Xu Chang; Yubing Gao; Qiang Fu; Shilin Hou; Hongxu Song; Hongyu Jin; Yuxuan Liu (Geotechnical and Geological Engineering, 2024)

Human reliability analysis of offshore high integrity pressure protection system based on improved CREAM and HCR integration method - Yang Yu; Shibo Wu; Yiqin Fu; Xiaowei Liu; Qingze Zeng; Hongyu Ding; Yu Pan; Yuke Wu; Hao Guo; Yuheng Yang (Ocean Engineering, 2024)

Blue light photobiomodulation induced osteosarcoma cell death by facilitating ferroptosis and eliciting an incomplete tumor cell stress response - Jiali Yang; Qiqi Fu; Hui Jiang; Hongyu Zhong; Hao Kuan Qin; Xiaojing Miao; Yinghua Li; Muqing Liu; Jinghui Yao (Journal of Photochemistry and Photobiology B: Biology, 2024)

Insight into the bacterial community composition of the plastisphere in diverse environments of a coastal salt marsh - Feng Yuan; Xinqing Zou; Qihang Liao; Teng Wang; Hexi Zhang; Yue Xue; Hongyu Chen; Yongcheng Ding; Ming Lu; Yuyang Song; Guanghe Fu (Environmental Pollution, 2024)

Microplastic pollution differences in freshwater river according to stream order: Insights from spatial distribution, annual load, and ecological assessment - Weikeng Luo; Hongyu Fu; Qiyuan Lu; Bowen Li; Xue Cao; Sifan Chen; Ruijuan Liu; Bin Tang; Xiao Yan; Jing Zheng (Journal of Environmental Management, 2024)

Experimental Study on an Innovative Method for Pre-split Blasting to Protect Withdrawal Roadways - Jun Yang; Xing Wu; Qiang Fu; Shilin Hou; Hongxu Song; Hongyu Jin; Yuxuan Liu; Jiarui Tang (Rock Mechanics and Rock Engineering, 2024)

Spatiotemporal successions of N, S, C, Fe, and As cycling genes in groundwater of a wetland ecosystem: Enhanced heterogeneity in wet season - Xianglong Chen; Yizhi Sheng; Guangcai Wang; Pengpeng Zhou; Fu Liao; Hairu Mao; Hongyu Zhang; Zhiyuan Qiao; Yuquan Wei (Water Research, 2024)

Microplastics: A potential proxy for tracing extreme flood events in estuarine environments - Hongyu Chen; Yu Cheng; Ying Wang; Yongcheng Ding; Chenglong Wang; Xuguang Feng; Qinya Fan; Feng Yuan; Guanghe Fu; Bingfei Gao; Kai Liu; Xinqing Zou (Science of The Total Environment, 2024)

A catchment-wide microplastic pollution investigation of the Yangtze River: The pollution and ecological risk of tributaries are non-negligible - Hongyu Chen; Teng Wang; Yongcheng Ding; Feng Yuan; Hexi Zhang; Chenglong Wang; Yameng Wang; Ying Wang; Yuyang Song; Guanghe Fu; Xinqing Zou (Journal of Hazardous Materials, 2024)

Biocontrol effect of the complex inoculants of Trichoderma and Bacillus amyloliquefaciens on chrysanthemum white rust - Anchan Kuang; Xiaoyun Fu; Zhihua Liu; Qi Chen; Ruibing Jin; Hongyu Mao (Biocatalysis and Agricultural Biotechnology, 2024)

Integrated scheduling problems of open shop and vehicle routing using an ensemble of group teaching optimization and simulated annealing - Jiaming Su; Yaping Fu; Kaizhou Gao; Hongyu Dong; Jianhui Mou (Swarm and Evolutionary Computation, 2023)

Deterministic factors modulating assembly of groundwater microbial community in a nitrogen-contaminated and hydraulically-connected river-lake-floodplain ecosystem - Zhiyuan Qiao; Yizhi Sheng; Guangcai Wang; Xianglong Chen; Fu Liao; Hairu Mao; Hongyu Zhang; Jiahui He; Yingxue Liu; Yilun Lin; Ying Yang (Journal of Environmental Management, 2023)

Metabolomics and metatranscriptomics reveal the influence mechanism of endogenous microbe (Staphylococcus succinus) inoculation on the flavor of fermented chili pepper - Yumeng Li; Xiaoqin Luo; Huan Guo; Jinrong Bai; Yue Xiao; Yuan Fu; Yanping Wu; Hongyu Wan; Yina Huang; Hong Gao (International Journal of Food Microbiology, 2023)

Sparse graph-regularized dictionary learning for full waveform inversion - Hongsun Fu; Hongyu Qi; Shujun Dong; Ran Hua (Computers & Geosciences, 2023)

Detecting the magical yellow-blue demarcation off the Yellow River Estuary from the space - Peng Li; Shenliang Chen; Hongyu Ji; Yaoshen Fan; Yutao Fu; Baichuan Ran; Yinghai Ke (Frontiers in Marine Science, 2023)
River deltas rank among the most ecologically and socio-economically valuable environments on the planet. The Yellow River Delta in China is not only home to young wetland ecosystem, but also to world-renowned tourism resources. One of these was the unique yellow-blue demarcation line (YBDL), formed in the Yellow River Estuary (YRE) as a result of the meeting of terrestrial sediment-laden river water and clear sea water, which had developed into a famous attraction and generated significant tourism revenues. Moreover, its distribution was of vital ecological and geomorphological importance due to association with the dynamics of estuarine turbidity plume. However, little is yet known about the dynamics and influencing factors of YBDL. In this study, we proposed an integrated method for extracting YBDL from satellite imagery and investigated the spatiotemporal distributions of YBDL during the flood season (June-October) from 2016 to 2022 using multi-source satellite imageries. The average relative error of our algorithm reached 10.53%. The results indicated that the YBDL started to frequently occur after 2018, mainly distributed within 10 km off the YRE, with two types of short straight and long curved shapes. July was the period with the highest frequency and most widespread distribution of YBDL. The riverine water and sediment discharge controlled 45.9% of the variations in YBDL length, and the extreme flooding, as well as the implementation of Water-Sediment Regulation Scheme, significantly increased the distribution extent of the YBDL. The morphology of river distributary mouths dominated the changes in the YBDL distribution centres, and the north distributary mouth experienced dramatic evolution in the last three years, with an increased YBDL distribution. Tidal currents could promote the development of YBDL at the front of the river mouth plumes while inhibiting the YBDL on the other side. This study is the first systematic investigation of the spatiotemporal evolutions and driving mechanisms of YBDL in the YRE, which could provide a reference for tourism planning and YRE National Park construction.

Revolutionizing Neurosurgery with GPT-4: A Leap Forward or Ethical Conundrum? - Wenbo Li; Mingshu Fu; Siyu Liu; Hongyu Yu (Annals of Biomedical Engineering, 2023)

Nitrogen species and microbial community coevolution along groundwater flowpath in the southwest of Poyang Lake area, China - Xianglong Chen; Guangcai Wang; Yizhi Sheng; Fu Liao; Hairu Mao; Bo Li; Hongyu Zhang; Zhiyuan Qiao; Jiahui He; Yingxue Liu; Yilun Lin; Ying Yang (Chemosphere, 2023)

Effects of microplastics on the toxicity of co-existing pollutants to fish: A meta-analysis - Feng Yuan; Hongyu Chen; Yongcheng Ding; Ying Wang; Qihang Liao; Teng Wang; Qinya Fan; Ziyue Feng; Chuchu Zhang; Guanghe Fu; Xinqing Zou (Water Research, 2023)

Gold-silver alloy hollow nanoshells-based lateral flow immunoassay for colorimetric, photothermal, and SERS tri-mode detection of SARS-CoV-2 neutralizing antibody - Tianyu Zhao; Penghui Liang; Jiaqi Ren; Jinyue Zhu; Xianning Yang; Hongyu Bian; Jingwen Li; Xiaofeng Cui; Chunhui Fu; Jinyan Xing; Congying Wen; Jingbin Zeng (Analytica Chimica Acta, 2023)

Determination of nitrogen sources and losses in surface runoff from different lands at a watershed scale - Zanfang Jin; Jiazheng Xiao; Hongyu Ye; Guowei Fu; Guangyao Li; Wangbin Wu; Feili Li (Environmental Science and Pollution Research, 2023)

Leonurine improves bovine oocyte maturation and subsequent embryonic development by reducing oxidative stress and improving mitochondrial function - Lv Zheng; Yuwen Luo; Dan Zhou; Hongyu Liu; Guizhen Zhou; Lin Meng; Yunpeng Hou; Changbin Liu; Jun Li; Xiangwei Fu (Theriogenology, 2023)

Spatial variability of source contributions to nitrate in regional groundwater based on the positive matrix factorization and Bayesian model - Hairu Mao; Guangcai Wang; Fu Liao; Zheming Shi; Hongyu Zhang; Xianglong Chen; Zhiyuan Qiao; Bo Li; Yunfei Bai (Journal of Hazardous Materials, 2023)

Exosomes from human urine-derived stem cells carry NRF1 to alleviate bladder fibrosis via regulating miR-301b-3p/TGFβR1 pathway - Junwei Wu; Xinxin Wang; Guoping Fu; Yiyuan Feng; Yan Wang; Guoxian Zhang; Yudong Wu; Lirong Zhang; Hongyu Meng; Jianguo Wen; Bing Zhang; Qingwei Wang (Molecular and Cellular Biochemistry, 2023)

SDGSAT-1: the world’s first scientific satellite for sustainable development goals - Huadong Guo; Changyong Dou; Hongyu Chen; Jianbo Liu; Bihong Fu; Xiaoming Li; Ziming Zou; Dong Liang (Science Bulletin, 2023)

Distribution of organophosphate ester fractions in sediment of the Eastern China Marginal Seas and the influencing factors - Qinya Fan; Hongyu Chen; Qihang Liao; Chuchu Zhang; Yongcheng Ding; Xinqing Zou; Guanghe Fu (Environmental Science and Pollution Research, 2022)

Application of regional citrate anticoagulation in patients at high risk of bleeding during intermittent hemodialysis: a prospective multicenter randomized controlled trial - Xiaoyan Tang; Dezheng Chen; Ling Zhang; Ping Fu; Yanxia Chen; Zhou Xiao; Xiangcheng Xiao; Weisheng Peng; Li Cheng; Yanmin Zhang; Hongbo Li; Kehui Li; et al. (Journal of Zhejiang University-SCIENCE B, 2022)

HDAC inhibitors improve CRISPR-mediated HDR editing efficiency in iPSCs - Jian-Ping Zhang; Zhi-Xue Yang; Feng Zhang; Ya-Wen Fu; Xin-Yue Dai; Wei Wen; Beldon Zhang; Hannah Choi; Wanqiu Chen; Meredith Brown; David Baylink; Lei Zhang; et al. (Science China Life Sciences, 2021)

Passivation and remediation of Pb and Cr in contaminated soil by sewage sludge biochar tubule - Lin Chen; Qi Ni; Yan Wu; Chuan Fu; Wei Ping; Hongyu Bai; Mengnan Li; Hongcheng Huang; Hanshuang Liu (Environmental Science and Pollution Research, 2021)

Phenotypic characteristics of ramie (Boehmeria nivea L) germplasm resources based on UAV remote sensing - Dandan Cui; Guoxian Cui; Ruifang Yang; Wei She; Yaoduan Liu; Hui Wang; Xiaohui Su; Jilong Wang; Wanhui Liu; Xinhui Wang; Jieyi Liu; Hongyu Fu (Genetic Resources and Crop Evolution, 2021)

Dynamic Change of Shanks Gene mRNA Expression and DNA Methylation in Epileptic Rat Model and Human Patients - Yujiao Fu; Du Liu; Jialing Guo; Hongyu Long; Wenbiao Xiao; Wei Xiao; Li Feng; Zhaohui Luo; Bo Xiao (Molecular Neurobiology, 2020)

Identification of a novel mutant spp1 that specifies the identity of inflorescence meristem in rice - Peizhou Xu; Asif Ali; Yun Li; Hongyu Zhang; Xiaoqiong Chen; Shaohong Fu; Yang Jin; Zhongwei Zhang; Shu Yuan; Xianjun Wu (Plant Biosystems, 2020)

Effect of male sterile and fertile cytoplasm on nuclear DNA methylation in hybrid rice - Asif Ali; Yun Li; Hui Chen; Peizhou Xu; Hongyu Zhang; Xiaoqiong Chen; Liao Yongxiang; Shaohong Fu; Tingkai Wu; Muhammad Zafar Iqbal; Muhammad Umer Farooq; Xianjun Wu (Acta Physiologiae Plantarum, 2019)

Assessing spatial and temporal variations in regional sustainability in mainland China from 2004 to 2014 - Wei Qiu; Fanlin Meng; Yuntao Wang; Guangtao Fu; Junguo He; Dragan Savic; Hongyu Zhao (Clean Technologies and Environmental Policy, 2018)

Morphological and genetic characterization of a new cytoplasmic male sterility system (oxa CMS) in stem mustard (Brassica juncea) - Shuangping Heng; Sansan Liu; Chunxiu Xia; HongYu Tang; Fei Xie; Tingdong Fu; Zhengjie Wan (Theoretical and Applied Genetics, 2018)

Secondary metabolites from marine-derived Streptomyces antibioticus strain H74-21 - Shuna Fu; Fan Wang; Hongyu Li; Yixuan Bao; Yu Yang; Huifang Shen; Birun Lin; Guangxiong Zhou (Natural Product Research, 2016)

Integration analysis of quantitative trait loci for resistance to Sclerotinia sclerotiorum in Brassica napus - Jiqiang Li; Zunkang Zhao; Alice Hayward; Hongyu Cheng; Donghui Fu (Euphytica, 2015)

Genetic mapping of a QTL controlling leaf width and grain number in rice - Yonghang Tian; Hongyu Zhang; Peizhou Xu; Xiaoqiong Chen; Yongxiang Liao; Baolin Han; Xiangbin Chen; Xiangdong Fu; Xianjun Wu (Euphytica, 2015)

Origin of hydrogen peroxide during the cowpea- Xanthomonas interaction - Yan Zhu; Yanhong Li; Ronghui Hu; Yani Zheng; Na Feng; Fu Chen; Jing Wang; Hongyu Li (Australasian Plant Pathology, 2012)

Combined Effect of Copper and Cadmium on Heavy Metal Ion Bioaccumulation and Antioxidant Enzymes Induction in Chlorella vulgaris - Haifeng Qian; Jingjing Li; Xiangjie Pan; Liwei Sun; Tao Lu; Hongyu Ran; Zhengwei Fu (Bulletin of Environmental Contamination and Toxicology, 2011)

Effect of salinity on hemolymph osmotic pressure, sodium concentration and Na+-K+-ATPase activity of gill of Chinese crab, Eriocheir sinensis - Hongyu Liu; Luqing Pan; Lü Fu (Journal of Ocean University of China, 2008)

Chemical composition, antimicrobial and antioxidant activities of the essential oil of Tibetan herbal medicine Dracocephalum heterophyllum Benth - ChunJiang Zhang; HongYu Li; Tian Yun; YongHong Fu; ChunMei Liu; Bu Gong; BenJia Neng (Natural Product Research, 2008)